The Impact of Social Media Use on Sexual Behavior Among Adolescents: Literature Review - Septiana Rahma Santi; Bagoes Widjanarko; Syamsulhuda Budi Musthofa (Media Publikasi Promosi Kesehatan Indonesia (MPPKI), 2024)
Introduction: One of the common sexual issues is sexual behavior, which is predominantly engaged in by adolescents aged 15-24. Approximately 15–20% of teenagers in Indonesia have had premarital sex, and around 2.3 million adolescents have undergone abortions. Additionally, there have been 1.7 million cases of unintended pregnancies (UP) and births among teenagers under the age of 24. The increase in sexual behavior among teenagers can be attributed to several factors, one of which is exposure to sexual content on social media. Most teenagers typically engage in sexual activities of their own volition, influenced by social media. Objective: The objective of this study is to understand the influence of social media use on adolescent sexual behavior. Method: This study is a scoping review using the PRISMA approach. The data sources for this research were obtained by accessing electronic databases or journal provider websites online from Google Scholar, PubMed, and Scopus, which have published articles in the last 5 years. Result: The ease of access to information about sexual behavior through social media can encourage teenagers to engage in sexual activities. However, social media can also provide information on preventing sexual behavior, helping teenagers avoid such actions. Therefore, the use of social media among teenagers has both positive and negative influences and impacts on sexual behavior. Conclusion: Social media use among adolescents has both positive and negative impacts. The negative impact of social media can include easy access to sexual or pornographic content, which may encourage adolescents to engage in sexual behavior. On the other hand, the positive impact is that adolescents can use social media as a source of information on sexual education to prevent them from engaging in sexual behavior.